Primary malignant melanoma of the uterine cervix treated with radical surgery and adjuvant chemo-radiation using temozolomide and cisplatin: a case report - Doke, Goter; Tsering, Shyam; Nobin, Hage; Gara, Dacto (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Primary malignant melanoma of the uterine cervix is a rare neoplasm and the overall prognosis of patients with this disease is very poor. Herein, authors report a case of 45-year-old woman who presented with vaginal bleeding for one months and examination showed an exophytic, 6 cm polypoid blackish-pigmented tumor on the cervix involving vaginal fornix. She underwent abdominal radical hysterectomy with bilateral salpingo-oophorectomy and pelvic lymphadenectomy and further received adjuvant concurrent chemo-radiation with cisplatin (CDDP) and temozolamide but died 7 months after surgery.